Zebrafish as a platform to evaluate the potential of lipidic nanoemulsions for gene therapy in cancer - Cascallar, María; Hurtado, Pablo; Lores, Saínza; Pensado-López, Alba; Quelle-Regaldie, Ana; Sánchez, Laura; Piñeiro, Roberto; de la Fuente, María (Frontiers in Pharmacology, 2022)
Gene therapy is a promising therapeutic approach that has grown significantly in the last decades, with gene nanomedicines reaching the clinics. However, it is still necessary to continue developing novel vectors able to carry, protect, and release the nucleic acids into the target cells, to respond to the widespread demand for new gene therapies to address current unmet clinical needs. We propose here the use of zebrafish embryos as an in vivo platform to evaluate the potential of newly developed nanosystems for gene therapy applications in cancer treatment. Zebrafish embryos have several advantages such as low maintenance costs, transparency, robustness, and a high homology with the human genome. In this work, a new type of putrescine sphingomyelin nanosystems (PSN), specifically designed for cancer gene therapy applications, was successfully characterized and demonstrated its potential for delivery of plasmid DNA (pDNA) and miRNA (miR). On one hand, we were able to validate a regulatory effect of the PSN/miR on gene expression after injection in embryos of 0 hpf. Additionally, experiments proved the potential of the model to study the transport of the associated nucleic acids (pDNA and miR) upon incubation in zebrafish water. The biodistribution of PSN/pDNA and PSN/miR in vivo was also assessed after microinjection into the zebrafish vasculature, demonstrating that the nucleic acids remained associated to the PSN in an in vivo environment, and could successfully reach disseminated cancer cells in zebrafish xenografts. Altogether, these results demonstrate the potential of zebrafish as an in vivo model to evaluate nanotechnology-based gene therapies for cancer treatment, as well as the capacity of the developed versatile PSN formulation for gene therapy applications.